Munition compound data for water samples collected from German and Danish waters of Baltic Sea during ALKOR cruise AL603 in October 2023 - Arinaitwe, Kenneth; Khoo, Siao Jean; Beck, Aaron; Greinert, Jens; Achterberg, Eric Pieter (PANGAEA, 2025)
This dataset consists of munition compound data from the analysis of water samples collected along a cruise track that went through German and Danish waters of the western Baltic Sea in October 2023 during ALKOR cruise AL603. The cruise track started and ended in the Bay of Kiel, via the Little Belt, Bay of Aarhus, Great Belt and Bay of Mecklenburg. Water column samples were collected from 99 stations. Surface and deep-water samples were collected using a rosette of Niskin bottles. A CTD sensor package was also mounted on the the Niskin rosette frame. Samples (1L) were extracted onboard onto solid phase extraction (SPE) columns. Munition compounds were eluted from the SPE columns using acetonitrile, concentrated and reconstituted in 50% methanol/water. The samples were analyzed by ultra high-performance liquid chromatography and high-resolution, atmospheric pressure chemical ionization mass spectrometry.
Keywords: Baltic Sea; Dumped munitions; Marine environment; Marine Pollution; Munition compounds; World War II